The Existence of the Death Penalty Sanction for Narcotics Criminal Acts Following the Enactment of Law Number 1 of 2023 on the Criminal Code - Oktarina, Surya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The enactment of Law Number 35 of 2009 on Narcotics introduced provisions imposing the death penalty for certain offences, while Law Number 1 of 2023 on the Criminal Code (KUHP) also regulates narcotics-related crimes under Articles 609, 610, and 611, with Article 610(2)(a) and (b) specifying the death penalty. This creates a conflict between the Narcotics Law, as a lex specialis, and the new Criminal Code, raising questions about the continued application of the death penalty for narcotics cases. Using a sociological and juridical-empirical approach, this research analyses the issue through the legal responsibility theory (grand theory), penal objectives theory (middle range theory), and applied theories of legal effectiveness, legal certainty, and criminal law politics. The findings reveal that the death penalty remains part of Indonesia's narcotics eradication strategy, aimed at deterrence, despite human rights concerns. Under Article 100 of the new Criminal Code, the death penalty is now an alternative sanction with a 10-year probation period, during which good behaviour may lead to commutation to life imprisonment by presidential decree. However, ambiguities exist regarding the authority to assess behaviour and the probation period’s alignment with criminal justice objectives, especially as narcotics trafficking remains a severe issue. The study concludes that the death penalty still exists but recommends harmonising the Narcotics Law and the Criminal Code to ensure legal certainty in its implementation.